ANALYSIS OF BUSINESS DEVELOPMENT STRATEGIES IN THE DIGITAL ERA: STUDY OF START-UP COMPANIES - Kartina Kartina; Abdul Razak Munir; Mursalim Nohong (Jurnal Ekonomi, 2023)
The development of digital technology has drastically changed the business landscape and provided new challenges and opportunities for companies, especially for start-up companies. This study aims to analyze business development strategies in the digital era with a focus on start-up companies. The research method used includes literature study and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). In this study, it was identified that the strengths of start-up companies include flexibility, innovation, and the ability to adapt quickly to market changes. Opportunities that exist in the digital era include the growth of e-commerce, the adoption of new technologies, and extensive online connectivity. However, the company also faces internal weaknesses such as limited resources, lack of experience, and limited infrastructure. Threats faced include intense competition, regulatory changes, and data security risks. Based on the SWOT analysis, several alternative business development strategies in the digital era were identified. Strategies based on strengths and opportunities include adopting new technologies quickly, correcting product or service innovation weaknesses, expanding connectivity through online networks and social media, and expanding the reach of products or services to new market segments or different industries.In addition, strategies based on weaknesses and opportunities include leveraging technological capabilities, investing in human resource development, and collaborating with third parties. Furthermore, strategies based on weaknesses and threats include improving data security, strengthening risk management, and increasing operational efficiency. The advice given in this research includes improving digital expertise, using data for decision making, focusing on customer experience, building, strengthening online presence, building partnership strategies, following market trends and developments, as well as maintaining sustainability and long-term development. This research contributes to start-ups in understanding the challenges and opportunities for business development in the digital era and provides strategic guidance to deal with them. Companies can adopt strategies that are relevant to their business characteristics and needs, so as to increase competitiveness, achieve sustainable growth, and achieve success in the digital era